An Anthropometric and Three-Dimensional Computed Tomographic Evaluation of Two-Point Fixation of Zygomatic Complex Fractures - Jo, Taehee; Kim, Junhyung (Archives of Plastic Surgery, 2014)
Background Maintaining stability and restoring the aesthetic appearance are the fundamental goals when managing zygomatic fractures. We aimed to evaluate the stability and anthropometric outcomes of zygomatic fracture patients who underwent two-point fixation involving the infraorbital rim and zygomaticomaxillary buttress via the transconjunctival and gingivobuccal approaches without any skin incisions.Methods We examined 15 zygomatic fracture patients who underwent two-point fixation during a 3-year period. Stability was evaluated using three-dimensional facial bone computed tomography. Superoinferior and anteroposterior displacement of the zygoma was quantified. The aesthetic appearance of the periorbital region was evaluated using indirect anthropometry with standardized clinical photographs. The ratios between the eye fissure height and width, and lower iris coverage ratio were used to evaluate aesthetical changes. The bony displacement and aesthetic ratios were analyzed using Wilcoxon or Friedman tests. The correlation between the preoperative zygoma position and anthropometric values was analyzed.Results The positions of the zygoma were similar to those on the contralateral side at the long-term follow-up. The preoperative anthropometric measurements on the fractured side differed from those on the contralateral side, although these values were close to the normal values at the long-term follow-up. Furthermore, we noted that the anteroposterior displacement strongly positively correlated with the lower iris coverage rate (Spearman's coefficient= 0.678, P=0.005).Conclusions Two-point fixation of zygomatic fractures achieved stable outcomes on long-term follow-up, and also appeared to be reliable in restoring the aesthetic appearance of the periorbital region.
Keywords: Zygomatic fractures; Fracture fixation; Anthropometry